2010
DOI: 10.1124/dmd.110.034603
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Activated C-Kinase 1 Regulates the Cell Surface Expression and Function of ATP Binding Cassette G2

Abstract: ABSTRACT:In a previous report, we identified the receptor for activated Ckinase 1 (RACK1) as a positive regulator of the cellular localization and expression of ATP-binding cassette B4, a phosphatidylcholine translocator expressed on the bile canalicular membrane. In the present study, we focused on the role of RACK1 on ATP-binding cassette G2 (ABCG2), which is responsible for the cellular extrusion of compounds including antitumor drugs. Protein expression of ABCG2 was up-regulated by RACK1 overexpression, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…PDZK1 is reported to directly interact with multidrug resistance-associated protein (MRP) 2, which is expressed in small intestine and has at least partially overlapped substrate specificity with BCRP (Kocher et al, 1999), although there has been no evidence that small intestinal MRP2 is regulated by PDZK1. Post-transcriptional regulation of BCRP has recently been reported in various types of cells (Ikebuchi et al, 2010;Nagai et al, 2011;Sugiyama et al, 2011). Nevertheless, the present findings are the first evidence that PDZK1 is a functional regulator for BCRP in vivo in small intestine.…”
Section: Discussioncontrasting
confidence: 45%
“…PDZK1 is reported to directly interact with multidrug resistance-associated protein (MRP) 2, which is expressed in small intestine and has at least partially overlapped substrate specificity with BCRP (Kocher et al, 1999), although there has been no evidence that small intestinal MRP2 is regulated by PDZK1. Post-transcriptional regulation of BCRP has recently been reported in various types of cells (Ikebuchi et al, 2010;Nagai et al, 2011;Sugiyama et al, 2011). Nevertheless, the present findings are the first evidence that PDZK1 is a functional regulator for BCRP in vivo in small intestine.…”
Section: Discussioncontrasting
confidence: 45%
“…1999). RACK1 regulates the plasma membrane localization of some proteins [35,36]. RACK1 may play an essential role not only in activating Aurora-A for mitotic commitment, but also recruitment of the activators to centrosome.…”
Section: Discussionmentioning
confidence: 99%
“… 14 It is confirmed that RACK1 can regulate several apoptosis-related genes and drug-related genes and then lead to the occurrence of chemotherapy resistance. 15 , 16 Furthermore, recent study showed that the expression level of RACK1 in tumor tissue was correlated with the chemoresistance of HCC. 12 In the current study, we aimed to evaluate the role of RACK1 in proliferation and its involvement in the underlying mechanism of chemotherapy resistance in ESCC.…”
Section: Introductionmentioning
confidence: 99%